Global and Russian M&A markets analysis: trends, drivers, deal success - M. Yu. Katalkina (Вестник университета)
M&A are still relevant and discussing according to global and Russian M&A statistics (value and count) and Management Tools & Trends survey, conducting by Bain & Company since 1993. Based on more than 10 surveys took place in different time M&A deals results were analyzed in different aspects, including top reasons why M&A have not generated expected value. Key M&A trends were analyzed: shift from scale deals to scope deals, complex corporate ecosystems occurring, time to close an M&A deal has risen in the last decade etc. As an illustration a few famous M&A failures were presented with results summary. Most important factors in achieving a successful M&A were defined and grouped in accordance with integration stages.